Pengaruh Romantisisme terhadap Tren Psikologis Maḥmūd ‘Abbās al-‘Aqqād dalam Kritik Sastra Arab Modern - Mutmainah, Mia; Tasnimah, Tatik Mariyatut (Al-Ma‘rifah, 2022)
This study aims to reveal the influence of the Western romanticism movement on the psychological style developed by Maḥmūd ‘Abbās al-‘Aqqād in assessing and understanding Arabic literary works in the modern era. This research is library research using the analytical-descriptive method. The result of this study shows that the psychological trend of al-‘Aqqād’s criticism is strongly influenced by the romanticism movement. Romanticism is a revolutionary movement in the artistic, literary, and intellectual fields that emerged in Europe as a form of resistance to the conditions around the 18th century. This movement emphasizes the individuality aspect to highlight the liberation of feelings and emotions. This aspect of individuality then became the basis of al-‘Aqqād’s criticism in assessing literary works which, according to him, were full of individual personalities. Thus, the psychological trend in Arabic literary criticism developed by al-‘Aqqād cannot be separated from the immense influence of the romanticism movement that emerged in the West. The results of this study increasingly show the significance of the West's role in the development of Arabic literary criticism in the modern era.